Re-thinking housing and mobility A European living lab for sustainable mobility in Munich. - Mück, Matthias; Helf, Christoph; Le Bris, Jessica (My University, 2017)
Die Arbeit befasst sich mit neuen nachhaltigen Mobilitätsformen für und in städtischen Zentrumsrandlagen am Beispiel des Münchener Projekts "Civitas Eccentric" innerhalb der europäischen "Civitas Initiative": Wohnen soll mit Mobilität verbunden werden, wobei der öffentliche Verkehr durch Mobilitätsangebote wie Carsharing, Bikesharing, Mitfahrer-Apps, On-Demand-Mobilität, spezielle Dienst für Blinde und Sehbehinderte etc. ergänzt wird. Die Ladeinfrastruktur für alle Formen der elektrischen Mobilität soll vor Ort vorhanden sein. Das Projekt soll zu nachhaltiger Mobilität und einer Attraktivitätssteigerung des Wohnstandortes führen.

The paper aims to describe the vision and implementation approach of a sustainable and innovative mobility and housing concept of a city district at the pericentral edge of Munich. Within the European CIVITAS initiative, the ECCENTRIC project demonstrates an innovative approach to mobilize residents by offering intermodal mobility and mobility on demand. With around 8000 new inhabitants and 12000 new employees within the next years, the transport system in the Munich living lab Domagkpark and Parkstadt Schwabing needs an integrative and innovative approach to ensure a functioning, ecologically compatible and socially acceptable mobility supply. Central objective is to increase quality of life in the district through a substantial roll-out of innovative mobility solutions, that reduce the use (and number) of private cars. With the implementation of various project measures in the field of sustainable and shared mobility, mobility management, city logistics and road security, a new model quarter for sustainable urban development and compatible mobility will be developed. Successful research findings aim to be implemented in future newly-built quarters of Munich and replicated in other European cities.
Keywords: Stadtumland; Vorstadt; Wohnstandort; Attraktivitätssteigerung; Berufspendlerverkehr; Erreichbarkeit; Mobilität; Verkehrsmittelwahl; Modal Split; Verkehrsangebot; E-Mobilität; Kommunikationstechnologie; Carsharing; Nachhaltige Mobilität; Reallabor; Bikesharing; On-Demand-Mobilität